International mobility experiences among Italian students: a cross-sectional survey comparing motivations towards high- versus low-income countries - Giovanni Putoto; Pietro Invernizzi; Maria Grazia Strepparava; Marco Bani; Selena Russo; Federico Zorzi; Alexia Del Greco; Stefano Ardenghi; Giulia Rampoldi (BMJ Open)
Objectives To examine the relevance of global health principles and identify motivational factors influencing international mobility experiences (IMEs) among Italian high school and undergraduate healthcare students, and to compare these motivations between high- and low-income country destinations.Design Cross-sectional study.Setting The study was conducted in Italy, with participants recruited from high schools during open days and from undergraduate healthcare programmes via email invitation.Participants A total of 423 participants (267 undergraduate healthcare students and 156 high school students aged 18 years or older) were included after excluding cases with incomplete control items; selection was based on voluntary participation with defined inclusion and exclusion criteria.Primary and secondary outcome measures The primary outcomes were the participants’ interest in and perceived probability of undertaking IMEs in high- versus low-income countries. Secondary measures included motivational factors assessed with the Multidimensional Motivations to Study Abroad Scale, empathy levels measured by the Brief Interpersonal Reactivity Index, personality traits assessed via the Ten Items Personality Inventory and self-reported knowledge and perceived importance of global health principles.Results In mixed analysis of variance analyses, motivations for IMEs differed by destination among both subgroups: better academic knowledge scored higher for high-income countries (high school (HS): 4.0±0.9 vs 3.3±1.0; university (Univ): 3.7±0.7 vs 2.9±0.7; p<0.001), as did language skills (HS: 4.5±0.7 vs 4.0±1.0; Univ: 4.2±0.5 vs 3.4±0.8; p<0.001) and career perspectives (HS: 4.2±0.9 vs 3.5±1.0; Univ: 3.6±0.6 vs 3.0±0.7; p<0.001). Cross-cultural interest was the only motivation higher for low-income destinations (HS: 4.4±0.8 vs 4.3±0.8; Univ: 4.2±0.6 vs 4.0±0.6; both p<0.01). Additionally, high school students reported greater overall interest in IMEs than undergraduates (4.03±1.04 vs 3.42±1.25; Z=−4.895, p<0.001). Structural equation modelling with bootstrapping confirmed these patterns (all path p<0.001), with 95% CIs indicating robust associations.Conclusions The findings suggest that tailored educational interventions integrating global health principles may enhance the motivation for IMEs, with distinct motivational drivers for high- versus low-income country destinations. Further longitudinal research is warranted to explore the temporal dynamics of these associations.